Acute Myocardial Infarction Caused by Gunshot Wound and ECG: Case Report - Özkan, Seda; Akdur, Okhan; Durukan, Polat; İkizceli, İbrahim; Avşaroğulları, Levent; Yücel, Murat; Sözüer, Erdoğan Mütevelli (Fırat University, 2007)
Gunshot injuries may cause acute myocardial infarction due to coronary artery damage, embolization of a bullet or pellet, and direct myocardial damage. A 46-year old man was brought to the emergency room with pellet injuries after being shot. Physical examination revealed a regular-edged and roundshaped wound with a diameter of 4 mm located 2 cm above the left nipple. The electrocardiogram showed marked ST segment elevation in the inferior leads and ST-segment depletion in V2, V3, V4, V5, DI, and AVL. Posteroanterior chest radiography disclosed a radiopaque round foreign body at the margin of the cardiac silhouette. Echocardiography showed posterolateral hypokinesia and minimal pericardial effusion. The patient was transferred to the operating room with the diagnosis of coronary injury and myocardial damage. The exploration revealed myocardial rupture on the anterior wall of the right ventricle. The damage was repaired and the patient was discharged on the postoperative 10 th day. An early diagnosis of cardiac injury can be made with an electrocardiogram obtained in emergency department. ©2007, Fırat University, Medical Faculty

Ateşli silah yaralanmalarına bağlı akut miyokard enfarktüsü; koroner arterin hasarına, mermi ve saçma tanesinin embolizasyonuna veya miyokardın doğrudan yaralanmasına bağlı oluşabilir. Kırk altı yaşında erkek hasta ateşli silah yaralanması sonucu toraksta saçma yaralanması ile acil servise getirildi. Fizik muayenede sol meme basının 2 cm üzerinde 4 mm çapında bir adet düzgün sınırlı muhtemel saçma tanesine bağlı ateşli silah yarası gözlendi. Hastanın çekilen elektrokardiyografisinde inferior derivasyonlarda ST segment yüksekliği; V2, V3, V4, V5, DI ve AVL de ST segment çökmesi saptandı. Posteroanterior akciğer grafisinde kalp gölgesi üzerinde radyoopak yabancı cisim gözlendi. Ekokardiyografide; posterolateral duvarda hipokinezi ve minimal perikardiyal mayi saptandı Hasta koroner yaralanma ve miyokardiyal hasar ön tanıları ile ameliyata alındı. Operasyonda sağ ventrikül ön duvarında defekt saptanarak tamir edilen hasta 10 gün sonra şifa ile taburcu edildi. Acil servislerde çekilen elektrokardiyografi ile kardiyak yaralanma tanısı erken dönemde konabilir. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Saçma Yaralanmasına Bağlı Akut Miyokard Enfarktüsü ve EKG